196k views
4 votes
Attached is the problem, and possible answers, please solve and check

Attached is the problem, and possible answers, please solve and check-example-1
User Alex Fox
by
4.9k points

1 Answer

2 votes

Answer:

Option B

Explanation:

Using the law of logarithms


n log x= log x^(n)

Therefore, since all the logs are to the same base, I will assume the base.

Also, when the bases are the same

log y+ log x= log (x+y)


\frac {1}{2}(log 4+ log 16)=log 4^(0.5)+log 16^(0.5)=log 2+log 4=log 6

Now log 6-log 2= log (6-2)= log 4

Therefore, option B is correct

User Antichris
by
4.9k points